Penerapan Metode Design Thinking Pada Perancangan Website SMKN 1 Tambang - Ahnaf Ikhsandi; Husni Laili; Junaidi Akbar; Yoyon Efendi (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
In the current era, most people look for school information only through online media, one of which is the school website. SMK N 1 TAMBANG is one of the vocational high schools in Kampar Regency. Tambang District, Rimbo Panjang Village, which was established in 2016 with 4 majors, namely, office administration, light vehicle engineering, motorcycle engineering and mechanical engineering. This school does not yet have a special website to introduce the school to the public through online media. Therefore, a user interface design is made that makes it easier for users to understand the appearance of the design to be designed. This special design design for the SMK N 1 TAMBANG school will be made using the design thinking method. Design thinking is the process of solving problems using a practical and creative solution approach using a user-side approach. The design design is made using figma and balsamiq tools. The results of this user interface design can be used by the school to create a special website for this school. The design of the user interface design using the Design thinking method is expected to help SMK N 1 TAMBANG in developing services for students and for prospective students in increasing school ratings to be better, so that schools can compete with other schools.